Analysis of Beta-Carotene Content Differences in Cempedak Jam using Traditional and Carbides Fruit Ripening Methods - Dahlan, Dwi Nur Aini (Universitas Dr Soetomo, 2019)
Cempedak fruit is one of the fruits that contain beta-carotene. Its ripening technique is estimated to impact the content of beta-carotene in the fruit after being processed into jam. The purpose of this research is to find out the correct type of ripening to produce the best quality cempedak jam that contains positive beta-carotene. Beta-carotene testing uses UV-Vis spectrophotometry. Data were analysed using the One Way Anava test on SPSS Statistics 21. The results showed that there were significant differences in the beta-carotene content between cempedak jam using traditional ripening with cempedak jam which was ripened by carbide. The beta carotene content of cempedak jam that has been traditionally ripened (average value: 0.42) has a higher beta-carotene content than cempedak jam that has been ripened by carbide (average value: 0.22).Keywords: Cempedak; beta-caroten content; Cempedak jam